MOTIVASI INTRINSIK MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM SEKOLAH TINGGI MA`ARIF MAGETAN DALAM MENGIKUTI PERKULIAHAN DARING PADA MASA PANDEMI COVID-19: Motivasi Intrinsik Perkuliahan Online - Arum Putri Rahayu (Jurnal Paradigma, 2020)
This research is a qualitative study which aimed to explore the intrinsik motivation owed by students of Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Ma`arif Magetan on on-line learning during this pandemic. Data were collected through interview which involving six respondents consist of two lecturers and four students. This research conducted by descriptive method and literature study. The research result stated that the intrinsik motivation of the students in the lower grade hadn’t showed off yet. That’s because of the feeling to increase their competence to be better than before is still absence from their mind. Another reason that occurs in the research is the student’s lower need to upgrade the knowledge only because they didn’t need it. The research results can be considered as a way to get the solution in increasing student’s intrinsik motivation in joining the classroom during the new normal era, also for the lecturer to find the better method and media in teaching learning processes.